Sem ordi não há porgueço e nóis sêmo desordero! : humor, paródia e vida urbana em Alvarenga e Ranchinho (1930/40) - Mazoti, Lays Matias (2011)
The humorous representation of the Brazilian history could always be perceived in several artistic formats: images, movies, literary texts, theatrical pieces and also in the music. In the folk music, beyond the conception the act of telling jokes , it was assumed, sporadically, a character scenic, performative and grotesquely. Thinking on this question, I seek in this work to analyze the main humorous productions of the hillbilly duo partner, observing, especially, a articulation between comic features used - satire and parody - with the current issues in the social environment of the 1930s and 1940s. However, you must understand artistic production within the field of various socio-cultural transformations that prevailed at the time, once it was from these very changes that hillbilly music could find space to face the urban prejudice city through appropriation of this new representation of the hillbilly ensuring, this way, its own identity.